2009
DOI: 10.1097/wnr.0b013e328324eb4d
|View full text |Cite
|
Sign up to set email alerts
|

The broken trust and cooperation in borderline personality disorder

Abstract: Trust and cooperation are essential features of human interpersonal transactions. Recent evidence suggests that these processes are related to brain areas implicated in social decision-making. These novel data provide a unique opportunity to characterize psychopathological conditions in which trust and cooperation are potentially impaired. Using economic games, independent investigations revealed that trust and cooperation are disrupted in patients with borderline personality disorder who have severe difficult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…The investor could share an amount of money with the trustee and the trustee could honor the investor's trust by returning some money. The authors reported reduced trusting behavior in BPD patients (see also Seres et al, 2009). Notably, these results were present only in the trust condition and not in the risk control condition where the investor could transfer money to a lottery.…”
Section: Experimental Methods Based On Game Theory Developed In Behavmentioning
confidence: 92%
See 1 more Smart Citation
“…The investor could share an amount of money with the trustee and the trustee could honor the investor's trust by returning some money. The authors reported reduced trusting behavior in BPD patients (see also Seres et al, 2009). Notably, these results were present only in the trust condition and not in the risk control condition where the investor could transfer money to a lottery.…”
Section: Experimental Methods Based On Game Theory Developed In Behavmentioning
confidence: 92%
“…Areas such as the anterior insula, the lateral orbitofrontal cortex and the right dorsolateral prefrontal cortex have been implicated as target regions of BPD (KingCasas et al, 2008;Seres et al, 2009;Spitzer et al, 2007). Furthermore, Berdahl (2010) suggested the involvement of the vmPFC in a neural network model of BPD.…”
Section: Discussionmentioning
confidence: 99%
“…First, when inflicting noncooperative exchanges on social partners, both healthy and BPD participants show increased insula activity, highlighting that the insula in BPD is specifically insensitive to level of trust received and likely related to abnormal perception of social partners’ actions. Second, subsequent work showed the decreased trust to be specific to BPD when compared with individuals with major depression, a common comorbid condition of BPD (67,68). Finally, individuals with BPD differ from control groups when making decisions involving social risk (trust game), but not nonsocial risk (gambles) (67,68).…”
Section: Multiplayer Economic Games Quantify the Behavioral Dynamics mentioning
confidence: 99%
“…In summary, alterations in executive functioning, declarative/explicit memory and decision making has widely been reported in BPD (Beblo et al, 2006;Black et al, 2009;Haaland et al, 2009;Haaland and Landrø, 2007;LeGris et al, 2012;Minzenberg et al, 2008;Rentrop et al, 2007;Richman and Unoka, 2015;Ruocco, 2005;Seres et al, 2009). In contrast, non-declarative, implicit learning has been neglected in this population.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent meta-analysis (Unoka and Richman, 2016) it was found a large overall effect size for global cognition deficit in BPD, with a large effect size for decision making, memory and executive functioning, and a small effect size for visuospatial abilities, attention, and verbal intelligence and processing speed (Beblo et al, 2006;Black et al, 2009;Haaland et al, 2009;Haaland and Landrø, 2007;LeGris et al, 2012;Minzenberg et al, 2008;Rentrop et al, 2007;Richman and Unoka, 2015;Ruocco, 2005;Seres et al, 2009). Although previous studies have focused on several aspects of declarative/explicit learning and memory (e.g., recognition and recall, the effect of emotions on learning) (Ebner-Priemer et al, 2009), to best of our knowledge, no study has investigated non-declarative, implicit learning yet.…”
Section: Introductionmentioning
confidence: 99%